Flexible textile strain sensors from polypyrrole-coated XLA™ elastic fibers. (May 2014) - Xue, Pu; Wang, Junpu; Tao, Xiaoming
Conductive fibers play an important role in flexible strain sensors. In this study, DOW XLA™ elastic fibers coated with polypyrrole (PPy) is investigated in their strain sensing behavior and corresponding mechanisms. A coating technique is developed based on surface treatment and chemical vapor deposition. The plasma surface treatment is applied, resulting in uniform and continuous coating on the fiber surface. Then, the strain-sensing behavior of the PPy-coated XLA fiber is investigated under both simple and cyclic tension. Compared with PPy-coated polyamide 6 and Lycra fibers, the sensitivity of the electrically conductive fibers on XLA fiber base is much higher and the measuring range is wider. With the help of the scanning electron microscope, the strain-sensing mechanisms are studied and the open–close mechanism of microcracks on the coating layer is identified.